Ferroelectric, dielectric and optic properties of Mn and Cr-doped Na0.5Bi0.5TiO3 single crystals. (18th August 2018) - Suchanicz, J.; Sitko, D.; Svirskas, Š.; Ivanov, M.; Kežionis, A.; Banys, J.; Czaja, P.; Kruzina, T. V.; Szczęsny, J.
Abstract: The results from Raman, pyroelectric, dielectric and ferroelectric investigations of Mn and Cr-doped Na0.5 Bi0.5 TiO3 (NBT) single crystals are presented. Influence of this substitution on the properties of NBT was observed. The influence manifests in several ways: (i) an increase of the electric conductivity, (ii) an increase of the remanent polarization and the decrease of coercive field, (iii) an improvement of pyroelectric properties and (iv) an increase of Tm temperature. Raman studies showed that substitution of a small amount of foreign ions affected local structure of the material. No evidence of the antiferroelectric phase was found in NBT-doped single crystals.